Conference Interpreting in the First International Labor Conference (Washington, D. C., 1919) - Baigorri-Jalón, Jesús (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractConference interpreting began at the 1919 Paris Peace Conference, where the League of Nations (LN) and its offsprings, the Permanent Court of International Justice and the International Labour Organization (ILO), were designed as tools of a new diplomacy by conferences. This meant the end of the virtual monopoly of French as the language of diplomacy and the presence of interpreters mediating between languages. This paper examines the context of the 1919 Washington International Labor Conference (ILC), the interpreting services, the interpreters’ working conditions, and proposes some conclusions. Sources include published records of the plenary meetings of the Washington ILC and unpublished documents from the Personnel files and other material from the archives of the ILO and the LN in Geneva.